Comparing college students' self-assessment of knowledge in organic chemistry to their actual performance - Karatjas, Andrew G. (Journal of Chemical Education, 2013)
Student self-assessment surveys were used to assess student study methods in organic chemistry courses. Surveys were given after examinations in the courses. Students that performed well on exams accurately predicted their exam scores. Students that did poorly were significantly off in their expectations.
Keywords: Chemical Education Research; Learning Theories; Organic Chemistry; Second-Year Undergraduate; Student-Centered Learning; Testing/Assessment; dept.che; peer-reviewed